2011
DOI: 10.1371/journal.ppat.1002115
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus Stimulates Release of Serotonin (5-HT) from Human Enterochromaffin Cells and Activates Brain Structures Involved in Nausea and Vomiting

Abstract: Rotavirus (RV) is the major cause of severe gastroenteritis in young children. A virus-encoded enterotoxin, NSP4 is proposed to play a major role in causing RV diarrhoea but how RV can induce emesis, a hallmark of the illness, remains unresolved. In this study we have addressed the hypothesis that RV-induced secretion of serotonin (5-hydroxytryptamine, 5-HT) by enterochromaffin (EC) cells plays a key role in the emetic reflex during RV infection resulting in activation of vagal afferent nerves connected to nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
165
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 166 publications
(176 citation statements)
references
References 75 publications
7
165
0
4
Order By: Relevance
“…Subsequently in Caco -2 cell line and other cell lines effects of NSP4 or its cleavage peptide (aa114-135) on calcium homeostasis, signal transduction pathways, serotonin secretion and Sodium Glucose symporter were studied. The findings have further reinforced its role as a toxin and virulence factor (Tian et al, 1994;Dong et al, 1997;Hagbom et al, 2011;Halaihel et al, 2000). Some studies have associated mutations in the gene with altered virulence (Zhang et al, 1998, Ball et al, 2013Tsugawa et al, 2014).…”
Section: Introductionmentioning
confidence: 83%
“…Subsequently in Caco -2 cell line and other cell lines effects of NSP4 or its cleavage peptide (aa114-135) on calcium homeostasis, signal transduction pathways, serotonin secretion and Sodium Glucose symporter were studied. The findings have further reinforced its role as a toxin and virulence factor (Tian et al, 1994;Dong et al, 1997;Hagbom et al, 2011;Halaihel et al, 2000). Some studies have associated mutations in the gene with altered virulence (Zhang et al, 1998, Ball et al, 2013Tsugawa et al, 2014).…”
Section: Introductionmentioning
confidence: 83%
“…Moreover, it has been shown that NSP4 and a cleavage fragment there of is secreted from infected cells 26--28 and that NSP4 can trigger pro--inflammatory cytokines from macrophages via Toll--like receptor--2 29 and stimulate serotonin (5--hydroxytryptamine, 5--HT) release from human EC cells 30 . Still, there are reports in the literature not being consistent with NSP4…”
Section: Proteins Involved In Replication Pathogenesis and Immune Rementioning
confidence: 99%
“…The myenteric plexus provides motor innervation to the circular muscle layer and the longitudinal muscle and regulates intestinal motility including peristalsis 142 . Over the years, it has become more and more evident that ENS is involved in rotavirus diarrhea 30,[74][75][76][77] . By blocking enteric neurotransmitters, that can act to induce active secretion (e.g.…”
Section: The Enteric Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the mortality from rotavirus infection results from excessive loss of fluids and electrolytes. Diarrhoea may be caused by several mechanisms, including malabsorption secondary to destruction of enterocytes, villus ischaemia, intestinal hypersecretion stimulated by the rotavirus non-structural enterotoxin protein NSP4, and activation of vagal afferent sensory neurons which transmit information to the hindbrain, leading to nausea and vomiting [50]. With regard to protective immunity, studies in humans and animals have reported correlations between rotavirus antibody levels and protection, the most consistent of which has been with rotavirus-specific serum IgA antibodies.…”
Section: Rotavirus Vaccinesmentioning
confidence: 99%